A Comparative Clinical Study of Two Varieties of Haritaki, Terminalia Chebula Retz. and Terminalia Pallida Brandis in Kaphaja Kasa (AYUSHDHARA, 2022)
Kasa, is a disease effecting Pranavaha srotas. It may develop as an independent disease or may be a Lakshana associated to other disease or sometimes may develop as Upadrava of a disease. It is the one of the most prevalent disorder that is annoying the individual and resulting in the change of lifestyle nowadays. Many Ayurvedic drugs are mentioned for the treatment of Kasa, of which Haritaki is one of the drugs, which is easily available and used extensively for the treatment. The present clinical study was carried out to study the comparative role of two types of Haritaki, Terminalia chebula Retz. and Terminalia pallida Brandis. in relieving Kaphaja Kasa. The Clinical trial was conducted on 30 patients between the age group 16 to 60 years. The study is a randomized clinical study and the patients were divided into two groups; each group consisted of 15 patients. Group-A patients were treated with Churnam tablets prepared of Terminalia chebula Retz. and Group-B patients were treated with Churnam tablets prepared of Terminalia pallida Brandis., Hot water was advised as Anupana. The results were analyzed statistically. The analysis suggested that the Group-B were more effective than Group-A in reducing the signs and symptoms of Kaphaja Kasa.